Investigation of genetic structure of angora goat by using starch gel electrophoretic method - Vahdettin Altunok; Mehmet Nizamlıoğlu; Zafer Bulut (Eurasian Journal of Veterinary Sciences)
In this present study, we determined the genetic structure of Angora and other breeds of goats. For this purpose, five different enzyme loci; superoxide dismutase (SOD), carbonic anhydrase 1 (CA1), esterase D (EsD), glutamic oxaloasetic transaminase (GOT), phosphogluconate dehydrogenase (PGD) and their 6 loci were examined by starch gel electrophoresis. In the study, red blood cell enzymes of 100 Angora goats from Yerköy (Animal Research Institute) and 19 goats belonging to 3 other breeds (Saanen, hair and Maltese goat) were used. For each of the enzyme systems appropriate buffers end chemicals for the activity staining were used in accordance with the information given in the literature. The observed bands of the izoenzymes were analysed. It is revealed that neither loci of SOD, Ca1, EsD, GOT, PGD of the individuals of Angora goat nor the individuals of other races exhibited variation. They displayed identical bands and they were all homozygotes. Therefore this study showed that 5 enzymes loci exhibited monomorphic. It is suggesting that, with respect to the loci studied, Angora goats do not differ from the other breeds of goats.